Women's autonomy and food security: Connecting the dots from the perspective of Indigenous women in rural Colombia - Kate Sinclair; Theresa Thompson-Colón; Alexandra Milena Bastidas-Granja; Sara Eloísa Del Castillo Matamoros; Eucaris Olaya; Hugo Melgar-Quiñonez (Elsevier, 2022)
There is a growing consensus that women's autonomy is positively related to food security. However, the evidence is inconsistent, and the nature of the pathways connecting the two factors remains unclear. Objective: To analyze the connection between women's autonomy and food security drawing from the perspective of rural Indigenous women in Nariño, Colombia. Methods: Focus group discussions and photovoice were conducted with 24 women. Results: Women elucidated numerous economic, social, cultural, and political constraints affecting their autonomy and limiting their ability to ensure a nutritionally adequate diet for their households. Economically, key constraints include the lack of remuneration for women's work, a lack of education, and restrictive gender roles and discrimination in the agricultural realm. Social constraints center around the inadequate recognition and valuation of women's work, gender stereotypical roles, and gender-based violence. With regard to the cultural domain, the women identified a lack of traditional knowledge transfer, a shift in the agricultural landscape, and environmental degradation as critical constraints. Further, they asserted that the dearth of political representation and participation of rural Indigenous women has direct implications for food security and facilitates the legitimization and institutionalization of the constraints identified across other areas. Conclusions: This study offers a nuanced understanding of the complexities linking food insecurity, autonomy, gender-inequality, discrimination, and poverty, while examining how intersectionality impacts these dynamic processes by recognizing women's points of view and perspectives-in this case-of one of the most vulnerable underserved, and under-researched segments of the Colombian population - Indigenous women.